Grover's Algorithm Extensions - A Systematic Literature Review - Amirul Asyraf Zhahir; Siti Munirah Mohd; Mohd Ilias M Shuhud; Nurhidaya Mohamad Jan; Bahari Idrus; Muhammad Mus-'Ab Anas Mohd Anas (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2026)
Indexed by MyCite